Bullying in elementary school and psychotic experiences at 18 years: a longitudinal, population-based cohort study. Issue 10 (July 2014) - Wolke, D.; Lereya, S. T.; Fisher, H. L.; Lewis, G.; Zammit, S.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Victims of bullying are at risk for psychotic experiences in early adolescence. It is unclear if this elevated risk extends into late adolescence. The aim of this study was to test whether bullying perpetration and victimization in elementary school predict psychotic experiences in late adolescence. Method The current study is based on the Avon Longitudinal Study of Parents and Children (ALSPAC), a prospective community-based study. A total of 4720 subjects with bullying perpetration and victimization were repeatedly assessed between the ages of 8 and 11 years by child and mother reports. Suspected or definite psychotic experiences were assessed with the Psychosis-Like Symptoms semi-structured interview at age 18 years. Results Controlling for child's gender, intelligence quotient at age 8 years, childhood behavioural and emotional problems, and also depression symptoms and psychotic experiences in early adolescence, victims [child report at 10 years: odds ratio (OR) 2.4, 95% confidence interval (CI) 1.6–3.4; mother report: OR 1.6, 95% CI 1.1–2.3], bully/victims (child report at 10 years: OR 3.1, 95% CI 1.7–5.8; mother: OR 2.9, 95% CI 1.7–5.0) and bullies (child report at 10 years: OR 4.9, 95% CI 1.3–17.7; mother: OR 1.2, 95% CI 0.46–3.1, n.s.) had a higher prevalence of psychotic experiences at age 18 years. Path analysis revealed that the association between peer victimization in childhood and psychotic experiences at age 18 years was only partially mediated by psychotic or depression symptoms in early adolescence. Conclusions Involvement in bullying, whether as victim, bully/victim or bully, may increase the risk of developing psychotic experiences in adolescence. Health professionals should ask routinely during consultations with children about their bullying of and by peers.